Extreme values of the shear modulus for hexagonal crystals. (November 2017) - Goldstein, Robert V.; Gorodtsov, Valentin A.; Komarova, Marina A.; Lisovenko, Dmitry S.
Abstract: In this paper, the variability of the shear modulus of hexagonal crystals was studied. Analytic expressions for the extreme values of the shear modulus were obtained. Numerical analysis of the extrema for hexagonal crystals was given on the basis of experimental data from the Landolt-Börnstein handbook. The greatest difference between the maximum and minimum values of the shear modulus was found for a layered crystal - graphite. A large difference between maximum and minimum is also characteristic for molybdenum disulphide. Classification scheme is proposed for the extreme values of shear modulus for hexagonal crystals as function of two dimensionless parameters. Graphical abstract: Highlights: Analytic expressions for the extreme values of the shear modulus were obtained. Numerical analysis of the extrema for hexagonal crystals was given. Classification scheme is proposed for the extreme values of shear modulus.